Enacting a People-Centred Curriculum in ELT With Teenage Learners - Darío Luis Banegas; Darío Luis Banegas (Profile: Issues in Teachers' Professional Development)
In this paper we reflect on the extent to which the learner-centred curriculum in English language teaching includes teachers and learners. We briefly describe the top-down nature of curriculum development in Argentina, then describe and discuss personal and collaborative explorations based on our identities as teachers of English in secondary education with a people-centred approach in the classroom. Through this paper we wish to highlight pedagogies and teacher strategies which are enacted for and from the classroom and built around both teachers and learners. Recommendations for policy makers are included.